2017
DOI: 10.1177/1049909117733473
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Placement of Inpatient Palliative Care Consult Orders Among Patients With Breast, Lung, and Colon Cancer in a Safety Net Hospital System

Abstract: In this cohort of patients in a safety net hospital, markers of pain, advanced disease, and poor prognosis were associated with placement of inpatient palliative care consult orders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Table 1 reports more recent detail of studies that conducted between 2015 and 2020 on advance healthcare planning and directives, palliative and hospice care that exclusively focused on or included non-Hispanic Blacks. 147,148,150 Palliative and Hospice Care…”
Section: Methodsmentioning
confidence: 99%
“…Table 1 reports more recent detail of studies that conducted between 2015 and 2020 on advance healthcare planning and directives, palliative and hospice care that exclusively focused on or included non-Hispanic Blacks. 147,148,150 Palliative and Hospice Care…”
Section: Methodsmentioning
confidence: 99%
“…First, most studies examined outcomes for people who were White, suggesting that this population may have been used as a comparator group. This approach has been criticized for centering Whiteness and placing many diverse groups within the Other [ 178 ] and perpetuating a broader system where White race is considered normative, and outcomes for individual racialized groups are obscured [ 218 ]. While White, Black, Hispanic/LatinX groups were examined in more than 50% of citations, others –– including Turtle Island (North American) Indigenous, Aboriginal Australian, Asian (multiple groups), Asian/Pacific Islander, Mixed, Māori, South Asian, East Asian, and Southeast Asian – were named in 25% or fewer studies.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence in support of early palliative care involvement has built a strong base, with studies showing that those who receive earlier intervention from palliative care have lower rates of hospitalizations. 5,8 For patients with advanced cancer, palliative care has been shown to improve health outcomes, positively impact quality of life, 5,7 reduce rates of depression, 5,7 decrease racial/ethnic disparities in hospice enrollment, 9 and result in better overall survival rates. 5 Similarly, data have shown that palliative care is associated with lower healthcare utilization at the end-of-life.…”
Section: Discussion Limitations and Future Directionsmentioning
confidence: 99%
“…These patients were hospitalized at Parkland Hospital from January 2010 to December 2010. Data were initially collected via an electronic medical record (EMR) review for a larger clinical study, 6,7 in which patients were identified from the EMR by ICD-9 codes. The investigators relied on data that could be extracted from discrete fields within the EMR; consequently, data on stage of disease were not available.…”
Section: Methodsmentioning
confidence: 99%